Analisa Spesifikasi Fluff, Pellet, dan Bricket Pelepah Kelapa Sawit sebagai Biomassa Co-firing untuk Pembangkit Listrik - Ari Aditia Sukma Sukma; Padil; Ahmad Fadli (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2023)
The abundance of palm frond waste in Indonesia makes it an ideal source as co-firing material to increase renewable energy consumption. Therefore, it is necessary to determine whether oil palm fronds in the form of fluff, pellets, and brickets can be used as co-firing fuel. This study also aims to see whether there are differences in the potential of hard and soft palm fronds as solid fuel for power plants, as well as to calculate its slagging and fouling risk. Palm fronds was dried and reduced in sized using a wood chipper then sifted with a 20 mesh sieve to obtain palm frond fluff, then the fluff was mixed with 22% tapioca adhesive (weight ratio of 20% of the biomass) to be molded into pellet. Meanwhile, wood brickets was prepared by pyrolyzing the hard fronds (T= 550oC, t= 5 min) and mixing the charcoal obtained with 22% tapioca adhesive (weight ratio of 30% of the biomass). From the results of the analysis carried out, it is known that palm frond bricket provides the best results with an NCV value of 7095 cal/g. On the other side, both hard frond fluff and soft frond fluff contains the same sulfur content (0.06%), thus the difference in using hard or soft fronds as co-firing fuel does not have much effect. Furthermore, based on the analysis of potential slagging and fouling, all types of oil palm frond samples studied are shown to have a low to medium risk level.